Self-assembly of hyaluronic acid-mediated tumor-targeting theranostic nanoparticles. (28th January 2021) - Zhou, Xiaoxuan; He, Chengbin; Liu, Min; Chen, Qingqing; Zhang, Lingjie; Xu, Xiaodan; Xu, Hongxia; Qian, Yue; Yu, Feidan; Wu, Yan; Han, Yuxin; Xiao, Bing; et al.
Abstract : A hyaluronic acid-coated and albumin-templated MnO2 and polydopamine hybrid nanoparticle for tumor-targeting imaging and therapy. Abstract : Theranostic nanoparticles (NPs) have emerged as promising candidates for cancer diagnosis and treatment. Manganese dioxide (MnO2 )-based NPs are potential contrast agents with excellent paramagnetic property and biocompatibility, exhibiting satisfactory magnetic resonance imaging (MRI) effects and biological safety. Recently, hyaluronic acid (HA) has gained increasing interest due to its tumor-targeting ability, which can improve the tumor affinity of manganese dioxide (MnO2 )-based NPs. In this study, HA-coated and albumin (BSA)-templated MnO2 and polydopamine hybrid nanoparticles (HMDNs) with tumor-targeting and superior imaging capability were fabricated via modifying the nanoparticles prepared by integrating dopamine polymerization and MnO2 biomineralization. The modification was found to enhance the cellular uptake of HMDNs by cancer cells. The prepared HMDN had high MRI contrasting capability with a longitudinal relaxivity of 22.2 mM −1 s −1 and strong photothermal therapy (PTT) effects with nearly complete tumor ablation under laser irradiation in vivo . HMDNs also showed effective clearance through kidneys, with no toxicity to important tissues. Therefore, HMDNs with superior imaging and PTT capability presented a new method to prepare tumor-targeting multifunctional nanotheranostics.